Les théories de l'action comme cadre interprétatif des politiques linguistiques - Gina Ioannitou (Recherches en didactique des langues et des cultures)
In this article I discuss the language policies of families as an element of linguistic socialization and individual development. This study is based on the theories of Action and views family as a social subsystem, dependent on other subsystems and on the social system as a whole. It focuses on the relationship between parental actions and beliefs and draws for that purpose on the description of factors which have an impact on individual action. Data obtained from interviews and questionnaires provide a presentation of the language policies of families in Greece, situating them within an enlarged conceptual network determining the use, appropriation and transmission of languages and cultures. Relying on Discourse Analysis tools and more specifically Motivational Analysis and Communicative Action, the study also presents the reasons that parents use to propound their choices in their discourse, as well as the ways in which these choices interfere with educational structures. It also questions the influence of family language policies on child socialization. The results of this study concern the intentionality which determines their actions and the way in which it is attributed to the different actors of language policies (parents, teachers, decision makers…). These various factors contribute to a better knowledge of the language policies of Greek and migrant families, from both a sociolinguistic and an action theory perspective.